2020
DOI: 10.3390/microorganisms8030456
|View full text |Cite|
|
Sign up to set email alerts
|

Fungal Microbiota of Sea Buckthorn Berries at Two Ripening Stages and Volatile Profiling of Potential Biocontrol Yeasts

Abstract: Sea buckthorn, Hippophae rhamnoides L., has considerable potential for landscape reclamation, food, medicinal, and cosmetics industries. In this study, we analyzed fungal microorganism populations associated with carposphere of sea buckthorn harvested in Lithuania. An amplicon metagenomic approach based on the ITS2 region of fungal rDNA was used to reveal the ripening-affected fungal community alterations on sea buckthorn berries. According to alpha and beta diversity analyses, depending on the ripening stage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 77 publications
1
14
0
Order By: Relevance
“…Obtained results are in concord with the previous studies accomplished with fresh-cut fruits such as apple, red and black currants, sea buckhorn, etc. [ 14 , 16 , 17 , 23 , 36 ]. Ascomycetous fungi distributed on the tested berries were mainly represented by Aureobasidium , Cladosporium , Metschnikowia , Hanseniaspora , and Taphrina genera.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Obtained results are in concord with the previous studies accomplished with fresh-cut fruits such as apple, red and black currants, sea buckhorn, etc. [ 14 , 16 , 17 , 23 , 36 ]. Ascomycetous fungi distributed on the tested berries were mainly represented by Aureobasidium , Cladosporium , Metschnikowia , Hanseniaspora , and Taphrina genera.…”
Section: Discussionmentioning
confidence: 99%
“…Ascomycetous fungi distributed on the tested berries were mainly represented by Aureobasidium , Cladosporium , Metschnikowia , Hanseniaspora , and Taphrina genera. It was previously demonstrated that intact berries were dominated by Aureobasidium , Taphrina , and Cladosporium fungi [ 14 , 37 ]. During the ripening process, fermentative ascomycetous microorganisms, such as Metschnikowia , Candida , and Hanseniaspora increased in frequency [ 14 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in the Funding section of [ 1 ] found an error. Consequently, the authors wish to correct “This research was funded by European Social Fund/European Regional Development Fund under grant agreement with the Research Council of Lithuania (LMTLT), grant number 09.3.3-LMT-K-712-01-0099.” to “This project has received funding from European Social Fund (project No 09.3.3-LMT-K-712-01-0099) under grant agreement with the Research Council of Lithuania (LMTLT).”…”
mentioning
confidence: 99%
“…The authors in the Funding section of [1] found an error. Consequently, the authors wish to correct "This research was funded by European Social Fund/European Regional Development Fund under grant agreement with the Research Council of Lithuania (LMTLT), grant number 09.3.3-LMT-K-712-01-0099."…”
mentioning
confidence: 99%